Resonant dynamics of three-dimensional skyrmionic textures in thin film multilayers - Titiksha Srivastava; Yanis Sassi; Fernando Ajejas; Aymeric Vecchiola; Igor Ngouagnia Yemeli; Hervé Hurdequint; Karim Bouzehouane; Nicolas Reyren; Vincent Cros; Thibaut Devolder; Joo-Von Kim; Grégoire de Loubens (APL Materials, 2023)
Skyrmions are topological magnetic solitons that exhibit a rich variety of dynamics, such as breathing and gyration, which can involve collective behavior in arrangements like skyrmion lattices. However, such localized excitations typically lie in the gap of the spin wave spectrum and do not couple to propagating modes. By combining magnetic force microscopy, broadband ferromagnetic resonance, and micromagnetics simulations, we show that in thin-film multilayers of [Pt/FeCoB/AlOx]20 a high-frequency (>12 GHz) mode accompanies the skyrmion lattice phase, which involves the coherent precession of the skyrmion cores that results in the generation of 50–80 nm wavelength spin waves flowing into the uniformly magnetized background. This observation is made possible by a Gilbert damping constant of ∼0.02, which is nearly an order of magnitude lower than in similar ultrathin materials. The simulations also reveal a complex three-dimensional spin structure of the skyrmion cores, which plays a key role for spin wave generation.